Processing and extraction methods of medicinal cannabis: a narrative review - Masoumeh Pourseyed Lazarjani; Owen Young; Lidya Kebede; Ali Seyfoddin (BMC, 2021)
Abstract Introduction As the cannabis industry transitions from a black market to a legal market, product development, and methods of extraction have become a focal point. To date, more than thousands of chemical constituents have been identified from the cannabis plant, all of which possess different chemical properties that require different conditions for preservation during drying and extraction. However, scientific publications that explore these areas for the cannabis plant are currently lacking. Method This is a narrative review paper which focuses on critiquing drying and extraction methods of Cannabis sativa L. plant. Relevant keywords such as medicinal cannabis, extraction, solvent, cannabinoids, and terpenes have been searched in PubMed, EMBASE, MEDLINE, Google Scholar, and Cochrane Library (Wiley) databases. Result To find relevant papers for this narrative review, 93 papers have been reviewed. Among them, 12 irrelevant papers were discarded. The excluded papers were either about hemp seed oil or hemp fiber and protein. Based on this review, solvent extraction is the most common method for cannabis plants. Although solventless and hydrodynamic extraction are known for their high yield and feasibility, more investigation is needed in these areas. Regarding the drying process, hang-drying is the most convenient method; however, it may be substituted by freeze-drying in the near future. Discussion This review analyses various drying and extraction processes to guide the selection of suitable methods for various types of cannabis products and applications. This is done by outlining traditional and modern methods of drying techniques, exploring the importance of solvents for extraction, visiting solventless extraction procedures, and finally comparing conventional and alternative methods of extraction. Conclusion In conclusion, based on the current knowledge, using organic solvents is the most convenient method for medicinal cannabis extraction. However, more research is needed for some of the drying and extraction methods. Also, developing a green and sustainable cannabis extraction method should be considered for future studies.